PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEUNTUNGAN, PERSEPSI KEAMANAN TERHADAP MINAT NASABAH BNI MENGGUNAKAN MOBILE BANKING - Wandi, Jefri (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2020)
The objective of this research is to analyze the effect of usability, profit, security simultaneously and partially on customer interest of BNI in using mobile banking at BNI Palu branch. It was a quantitative research used multiple linear regression analysis method with a total of 100 respondents. The results of this researchshow thatusability, profit and security perceptions simultaneously have a significant effect on customer interest of BNI in using mobile banking at BNI Palu branch. Usability perception has a significant effect on customer interest of BNI in using mobile banking at BNI Palu branch.Profit perception has a significant effect on customer interest of BNI in using mobile banking at BNI Palu branch. Security perception has a significant effect on customer interest of BNI in using mobile banking at BNI Palu branch.